Avaliação do desempenho no sprint e salto em distância pós-ativação em atletas treinados - Silva, Devisson dos Santos (2023)
Introduction: Performance can be influenced by acute stimuli. Evidence suggests that warm-up can be a strategy to post-activation performance enhancement during competition. Objectives: To verify the acute effect of drop jump and dynamic stretching on sprint performance in sprinters and jumpers, and the inclusion of drop jump in the warm-up for the long jump. Methodology: This study used two investigations: 1) A randomized crossover study with thirteen volunteer male jumpers and sprinters (19 ± 2 years old; 177 ± 7 cm; 71.7 ± 5.6 kg). The athletes performed three different conditions after a standardized warm-up: dynamic stretching (DS)+ drop jump(DJ), DJ+DS, and control (no exercise). Performance in the 40 m sprint was evaluated pre- and post-intervention, considering the phases of acceleration (0 to 20 m) and maximum speed (20 to 40 m). Data were analyzed using two-way ANOVA for repeated measures and Pearson's test. 2) Intervention study in a competitive environment assessing pre and post-drop jumps with the participation of 11 male volunteer jumpers (19.0 ± 2.0 years old; 178.0 ± 9.0 cm; 73.1 ± 8.9 kg). The athletes performed five drop jumps, two minutes (1'45-2'15 min) before the second, and fourth attempts. Jump distance, approach velocity, duration, vertical velocity, horizontal velocity, and departure angle were evaluated. Data were analyzed using ANOVA for repeated measures, paired t-test, and Pearson's test. Results: When performance in the 40 m sprint was evaluated (study 1), there was no effect of any factor on 40 m sprint performance. Performance in the final acceleration phase of the sprint post-intervention was better than baseline in the DS+DJ condition (8.79 ± 0.43 vs. 8.91 ± 0.35 m/s; p=0.015). However, postintervention acceleration ability was worse than baseline in the DJ+DS condition (6.26 ± 0.25 vs. 6.22 ±0.26 m/s; p=0.002). There was a negative correlation between lower limb power and improvement in maximum sprint speed (r = -0.741; p=0.004). In the investigation related to the long jump (study 2), it was found that the performance of the second (5.63 ± 0.43 cm) and fourth (5.71 ± 0.34 cm) jumps performed post-activation were higher than the first (5.54 ± 0.45 cm) in the control condition, p=0.02, and p=0.01, respectively. Differences in take-off vertical velocity were found between the fourth (1.55 ± 0.21 m/s) and first attempt (1.30 ± 0.40 m/s), p=0.006. Jump performance showed a positive correlation with approach velocity, vertical velocity, and take-off duration. The mean performance in the post-activation jump (5.67 ± 0.38 cm) was superior to the control condition (5.59 ± 0.44 cm), p= 0.02, g=0.19. Conclusion: The use of drop jumps and dynamic stretching did not promote improvement in the performance of the 40 m sprint, however, the performance in the final acceleration phase of the 40 m sprint was improved after the use of dynamic stretching and drop jumps in this order. The inclusion of drop jumps in the warm-up of jumpers promotes improvement in the performance of the long jump, which could be explained by the increase in take-off vertical velocity in the jump.